TFE Terpolymers: Once Promising – Are There Still Perspectives in the 21st Century: Synthesis, Characterization, and Properties‐Part I - Ok, Salim; Steinhart, Martin; Scheler, Ulrich; Améduri, Bruno (Macromolecular rapid communications., 2024)
Polytetrafluoroethylene (PTFE) exhibits outstanding properties such as high‐temperature stability, low surface tension, and chemical resistance against most solvents, strong acids, and bases. However, these traits make it challenging to subject PTFE to standard polymer processing procedures, such as thermoforming and hot incremental forming. While polymer processing at temperatures above the melting point of PTFE is already demanding, the typically large molar mass of PTFE results in extremely high melt viscosities, complicating the processing of PTFE. Also, PTFE tends to decompose at temperatures close to its melting point. Therefore, fluoropolymers obtained by copolymerizing tetrafluoroethylene (TFE) with various co‐monomers are studied as alternatives to PTFE (e.g., fluorinated ethylene‐propylene (FEP)), combining its advantages with better processability. TFE terpolymers have emerged as desirable PTFE alternatives. This review provides an overview of the synthesis with various comonomers and microstructural analysis of PTFE terpolymers and the relationships between the microstructures of TFE terpolymers and their properties. PTFE decomposes at temperatures close to its melting point. Therefore, TFE terpolymers have emerged as desirable PTFE alternatives, where these TFE terpolymers combine PTFE's advantages with better processability. Currently, fluoropolymers have reached a new era. The present review summarizes the synthesis, detailed characterization, and structure‐property correlations of the fluoropolymers and ends with a future perspective on the use of fluoropolymers.